Analisis Wacana Pemberitaan Vaksin MR (Measles Rubella) pada Website Tribun Sumsel - Nuraida Nuraida; Lara Agristaria (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2019)
One of the news topics that attracts readers is the pros and cons of the MR (Measles Rubella) vaccine. The MR (Measles Rubella) vaccine news discourse that has been published on the South Sumatra Tribune website was analyzed with the Teun A Van Dijk model analysis with a six-structure approach namely: thematic, schematic, semantic, syntactic,stylistic, and rhetorical. Of the three discourses that have been analyzed using the Teun A Van Dijk model, it is known that the development of the community is controversial with the MR (Measles Rubella) vaccine because it has not yet received the halal label from the MUI (Indonesian Ulama Council) of South Sumatra Province, especially Palembang City. MUI has learned that the MR vaccine contains elements of pigs and human organs which are in principle unclean. Therefore the South Sumatra MUI ordered the Health Office to stop giving MR vaccine until waiting for a decision from the central MUI. At this time the MR vaccine is allowed (permissible) only in an emergency.